2021
DOI: 10.3390/pathogens10020136
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carriage and Antimicrobial Susceptibility Profile of Staphylococcus aureus among Children under Five Years in Accra

Abstract: This cross-sectional study investigated the S. aureus and methicillin-resistant S. aureus (MRSA) nasopharyngeal carriage epidemiology in Accra approximately five years post-pneumococcal conjugate vaccine introduction in the country. Archived nasopharyngeal swabs collected from 410 children aged under five years old were bacteriologically cultured. The resultant S. aureus isolates were subjected to antimicrobial susceptibility testing and screening for carriage of the mecA and LukF-PV (pvl) genes, following sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
(134 reference statements)
2
6
3
Order By: Relevance
“…The highest proportion of S. aureus resistance was recorded against penicillin (100%). Previous studies in the country have also reported similar rates for the organism [ 30 , 53 , 54 , 56 , 57 , 58 ], and this may be due to the wide usage of the antibiotic. These studies additionally recorded similar antimicrobial resistance rates for the other antimicrobials investigated [ 30 , 53 , 54 , 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The highest proportion of S. aureus resistance was recorded against penicillin (100%). Previous studies in the country have also reported similar rates for the organism [ 30 , 53 , 54 , 56 , 57 , 58 ], and this may be due to the wide usage of the antibiotic. These studies additionally recorded similar antimicrobial resistance rates for the other antimicrobials investigated [ 30 , 53 , 54 , 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies in the country have also reported similar rates for the organism [ 30 , 53 , 54 , 56 , 57 , 58 ], and this may be due to the wide usage of the antibiotic. These studies additionally recorded similar antimicrobial resistance rates for the other antimicrobials investigated [ 30 , 53 , 54 , 56 , 57 , 58 ]. Of particular interest is the high resistance displayed against cotrimoxazole in the current study, given its usage in prophylaxis.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This was a cross-sectional study involving retrospective analysis of frozen swab samples stored at −80 °C in skim milk tryptone glucose glycerol broth (STGG). These samples were collected as part of a previous study conducted in 2016 which examined carriage rates of S. pneumoniae and S. aureus [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, S. pneumoniae [ 16 ] and S . aureus [ 17 ] were isolated, antimicrobial susceptibility testing and serotyping were performed, and the data were analysed using standard techniques. For the purpose of this study, GNB were isolated, and antimicrobial susceptibility testing was performed.…”
Section: Methodsmentioning
confidence: 99%